Metode Peer-Assisted Learning Srategies (PALS) untuk Meningkatkan Hasil Belajar Matematika Siswa SMK - Riska Kahaning Sari; Budi Santosa (Gammath : Jurnal Ilmiah Program Studi Pendidikan Matematika, 2023)
Peer-Assisted Learning Strategies (PALS) is a teaching method that has been relatively underexplored in current research. PALS aims to enhance the academic performance of 10th-grade students at TJKT 2 Vocational School, Muhammadiyah 5 Jember, and to determine the impact of utilizing Peer-Assisted Learning Strategies (PALS) on the mathematical learning outcomes of these students. This method is a form of cooperative learning with peer assistance serving as tutors. This study employs an action research approach to improve the teaching process. The research process involves several steps, including initial idea generation, pre-survey, diagnosis, planning, action implementation, observation, and reflection. Students are organized into several groups to carry out the Peer-Assisted Learning Strategies (PALS) learning method. The subjects of this research are 24 students in the 10th-grade Computer Networking and Telecommunications program at SMK Muhammadiyah 5 Jember during the second semester of the 2022/2023 academic year. Data collection is conducted through mathematics test results. The research findings indicate that, prior to the intervention, only 38% of the students passed the assessment, while 62% did not. After implementing the Peer-Assisted Learning Strategies (PALS) method, the mathematical learning outcomes significantly improved, with 75% of the students passing and 25% remaining below the passing threshold. Based on these results, it can be concluded that the implementation of Peer-Assisted Learning Strategies (PALS) can enhance mathematics learning.